Morphological and Syntactical Error Analysis on Students' Procedure Text Writings - Laila Desnaranti (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2018)
The purpose of the research is to analyze morphological and syntactical errors in a procedure text that made by the students in private vocational school in Bogor. The research method that used to analyze morphological and syntactical error in the procedure text that made by the students is descriptive qualitative method that based only on a few procedure texts. After the researcher analyze the procedure text, the researcher found that the students still make the morphological and syntactical errors in their writings.